Dewi Sri Dalam Kepercayaan Masyarakat Indonesia - Titi Surti Nastiti (Tumotowa, 2020)
In Hinduism, Goddess Sri is known as the wife of Lord Vishnu. There were found several statues made from stone and bronze called “Dewi Sri” (Goddess Sri) in Indonesia. Judging from the hand positions and attributes of the statue of Goddess Sri found in Indonesia, iconographically they are different from Goddess Sri statue found in India. The assumption is that the depiction of Dewi Sri in Indonesia has always been related as the Goddess of Fertility or the Goddess of Rice. Paying homage to the Goddess of Rice or the Goddess of Fertility had already existed before Hindu-Buddhist influences came to the archipelago. Therefore, when the siplin (statue maker) depicting Goddess Sri as the Goddess of Rice, the siplin has a different concept from Goddes Sri as the wife of Lord Vishnu, although Goddess Sri as the Goddess of Rice is also believed to be the wife of Lord Vishnu. The depiction of Goddess Sri is inseparable from the concept of her as the Goddess of Rice that has been worshipped from the Prehistoric Period, therefore Goddess Sri has a distinctive attribute that depicts this, which is her left hand holding a sprig of rice. The purpose of writing this paper is to find out the description of Goddess Sri as the Goddess of Rice in the beliefs of Indonesian society and its tradition up to now. This paper used a qualitative and analytical descriptive method, while to describe the statue iconographic analysis is used. From the result of this study, it can be described how the belief of Goddess Sri in the Indonesian Society as a Goddess of Rice which is very closely related to fertility plays an important role in agriculture.